Biomass-mediated ZSM-5 zeolite synthesis: when self-assembly allows to cross the Si/Al lower limit. Issue 31 (11th July 2018) - Pereira, Marcelo Maciel; Gomes, Elisa Silva; Silva, Alessandra Vieira; Pinar, Ana Belen; Willinger, Marc-Georg; Shanmugam, Sangaraju; Chizallet, Céline; Laugel, Guillaume; Losch, Pit; Louis, Benoît
Abstract : Biomass-mediated syntheses of ZSM-5 zeolites allowed crossing low Si/Al barrier, inducing high acidity, hence remarkably improving catalyst performance. Abstract : A family of Al-rich ZSM-5 zeolites with Si/Al = 8 ± 0.5 was prepared according to a biomass-mediated supramolecular approach. A combination of advanced characterisation techniques and periodic density functional theory (DFT) calculations unraveled the purity and stability of un-expected Al-enriched ZSM-5 structures, hence allowing to cross the frontier of Si/Al lower limit. In addition, these Al-rich ZSM-5 zeolites demonstrated high catalytic activity in n -hexane cracking and methanol conversion into hydrocarbons, being in line with the presence of numerous Brønsted acid sites.